Cumulative sum learning curves guiding multicenter multidisciplinary quality improvement of EUS-guided tissue acquisition of solid pancreatic lesions - Hannah M. Schutz (Endoscopy International Open, 2022)
Background and study aims In this study, we evaluated the performance of community hospitals involved in the Dutch quality in endosonography team regarding yield of endoscopic ultrasound (EUS)-guided tissue acquisition (TA) of solid pancreatic lesions using cumulative sum (CUSUM) learning curves. The aims were to assess trends in quality over time and explore potential benefits of CUSUM as a feedback-tool. Patients and methods All consecutive EUS-guided TA procedures for solid pancreatic lesions were registered in five community hospitals between 2015 and  2018. CUSUM learning curves were plotted for overall performance and for performance per center. The American Society of Gastrointestinal Endoscopy-defined key performance indicators, rate of adequate sample (RAS), and diagnostic yield of malignancy (DYM) were used for this purpose. Feedback regarding performance was provided on multiple occasions at regional interest group meetings during the study period. Results A total of 431 EUS-guided TA procedures in 403 patients were included in this study. The overall and per center CUSUM curves for RAS improved over time. CUSUM curves for DYM revealed gradual improvement, reaching the predefined performance target (70 %) overall, and in three of five contributing centers in 2018. Analysis of a sudden downslope development in the CUSUM curve of DYM in one center revealed temporary absence of a senior cytopathologist to have had a temporary negative impact on performance. Conclusions CUSUM-derived learning curves allow for assessment of best practices by comparison among peers in a multidisciplinary multicenter quality improvement initiative and proved to be a valuable and easy-to-interpret means to evaluate EUS performance over time.